Solve for x
x = \frac{\sqrt{3889} + 67}{10} \approx 12.936184731
x=\frac{67-\sqrt{3889}}{10}\approx 0.463815269
Graph
Share
Copied to clipboard
-5x^{2}+67x-30=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-67±\sqrt{67^{2}-4\left(-5\right)\left(-30\right)}}{2\left(-5\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -5 for a, 67 for b, and -30 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-67±\sqrt{4489-4\left(-5\right)\left(-30\right)}}{2\left(-5\right)}
Square 67.
x=\frac{-67±\sqrt{4489+20\left(-30\right)}}{2\left(-5\right)}
Multiply -4 times -5.
x=\frac{-67±\sqrt{4489-600}}{2\left(-5\right)}
Multiply 20 times -30.
x=\frac{-67±\sqrt{3889}}{2\left(-5\right)}
Add 4489 to -600.
x=\frac{-67±\sqrt{3889}}{-10}
Multiply 2 times -5.
x=\frac{\sqrt{3889}-67}{-10}
Now solve the equation x=\frac{-67±\sqrt{3889}}{-10} when ± is plus. Add -67 to \sqrt{3889}.
x=\frac{67-\sqrt{3889}}{10}
Divide -67+\sqrt{3889} by -10.
x=\frac{-\sqrt{3889}-67}{-10}
Now solve the equation x=\frac{-67±\sqrt{3889}}{-10} when ± is minus. Subtract \sqrt{3889} from -67.
x=\frac{\sqrt{3889}+67}{10}
Divide -67-\sqrt{3889} by -10.
x=\frac{67-\sqrt{3889}}{10} x=\frac{\sqrt{3889}+67}{10}
The equation is now solved.
-5x^{2}+67x-30=0
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
-5x^{2}+67x-30-\left(-30\right)=-\left(-30\right)
Add 30 to both sides of the equation.
-5x^{2}+67x=-\left(-30\right)
Subtracting -30 from itself leaves 0.
-5x^{2}+67x=30
Subtract -30 from 0.
\frac{-5x^{2}+67x}{-5}=\frac{30}{-5}
Divide both sides by -5.
x^{2}+\frac{67}{-5}x=\frac{30}{-5}
Dividing by -5 undoes the multiplication by -5.
x^{2}-\frac{67}{5}x=\frac{30}{-5}
Divide 67 by -5.
x^{2}-\frac{67}{5}x=-6
Divide 30 by -5.
x^{2}-\frac{67}{5}x+\left(-\frac{67}{10}\right)^{2}=-6+\left(-\frac{67}{10}\right)^{2}
Divide -\frac{67}{5}, the coefficient of the x term, by 2 to get -\frac{67}{10}. Then add the square of -\frac{67}{10} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}-\frac{67}{5}x+\frac{4489}{100}=-6+\frac{4489}{100}
Square -\frac{67}{10} by squaring both the numerator and the denominator of the fraction.
x^{2}-\frac{67}{5}x+\frac{4489}{100}=\frac{3889}{100}
Add -6 to \frac{4489}{100}.
\left(x-\frac{67}{10}\right)^{2}=\frac{3889}{100}
Factor x^{2}-\frac{67}{5}x+\frac{4489}{100}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x-\frac{67}{10}\right)^{2}}=\sqrt{\frac{3889}{100}}
Take the square root of both sides of the equation.
x-\frac{67}{10}=\frac{\sqrt{3889}}{10} x-\frac{67}{10}=-\frac{\sqrt{3889}}{10}
Simplify.
x=\frac{\sqrt{3889}+67}{10} x=\frac{67-\sqrt{3889}}{10}
Add \frac{67}{10} to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}